Fluid Therapy in Acute Pancreatitis. A Systematic Review of Literature - Solanki, Nicholas S; Barreto, Savio George (JOP. Journal of the Pancreas, 2011)
No abstract available. Image: Royal Adelaide Hospital. Adelaide, South Australia, Australia.